ANALISIS SEKTOR UNGGULAN DAN PERGESERAN PANGSA SEKTOR-SEKTOR EKONOMI DI KABUPATEN PASAMAN BARAT - Eva Oktarina; Alpon Satrianto (Universitas Negeri Padang, 2019)
This study aims to analyze the leading sectors in West Pasaman District and find the structure change economic in West Pasaman District. The method used in this study is Analytical Hierarchy Process (AHP) to see the leading sector and Shift Share Analysis to see a chage in economic structure in West Pasaman District. This type of research is descriptive and quantitative research with the data used are primary data and PDRB data from 2012-2016. The results showed that (1) the leading sector in West Pasaman District was agriculture, forestry and fisheries (2) there was a change in the economic structure in West Pasaman District from the agricultural sector to the industrial sector and services